BIO-ADSORBEN BERBAHAN DASAR LIMBAH AMPAS TEH (CAMELLIA SINENSIS) SEBAGAI AGENT PENYERAP LOGAM BERAT FE DAN PB PADA AIR SUNGAI - Azzahra, Rizanti Fadila; Taufik, Muhammad (KINETIKA, 2020)
The aims of this study were to examine the effectiveness of tea waste as adsorbent by variation of difference in mass of adsorbent which is 0,25, 0,50, and 0,75 grams and contacting time is 5,10 and 15 minutes. This study began with downsizing the size of tea waste become 200 mesh, then was performed a chemical activation by soaking tea waste with HCl 0,1 N for Â± 24 hours. The adsorption was performed by contacting adsorbent with a solution of sample is based on contacting time and mass of adsorbent. The concentration of resulting solution was analyzed using AAS. Based on the result, the highest Fe absorption percentage can be obtained from waste tea leaves bioadsorbent that is 80,78% at 0,75 gram adsorbent weight with 15 minute contact time, while highest Pb absorption percentage can be obtained from tea waste adsorbent that is 93,75% at 0,75 gram adsorbent weight with 15 minute contact time.